2018
DOI: 10.3904/kjim.2016.323
|View full text |Cite
|
Sign up to set email alerts
|

Management of carbapenem-resistant Acinetobacter baumannii epidemic in an intensive care unit using multifaceted intervention strategy

Abstract: Background/AimsWe evaluated the effects of a multifaceted intervention for controlling a carbapenem-resistant Acinetobacter baumannii (CRAB) epidemic in an intensive care unit (ICU) with no restrictions on carbapenem use.MethodsThis study was conducted in a medical ICU between April 2012 and June 2016. The baseline infection control programs included surveillance cultures, contact precautions, and environmental cleaning. However, increases in the detection of CRAB isolates beginning in May 2013 led to the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…24 CRAB outbreaks are notoriously difficult to control, mostly due to carriage persistence 23 in parallel with the characteristic, prolonged hospitalization of carriers and survival of the bacteria in the environment. Our intervention, like others 25,26 demonstrates that, by using a multifaceted infection control program, marked reduction in CRAB acquisition, accompanied by interruption of CRAB transmission can be achieved. Such an intervention, demanding increased manpower and resources, could not have been executed without hospital and ward management support.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…24 CRAB outbreaks are notoriously difficult to control, mostly due to carriage persistence 23 in parallel with the characteristic, prolonged hospitalization of carriers and survival of the bacteria in the environment. Our intervention, like others 25,26 demonstrates that, by using a multifaceted infection control program, marked reduction in CRAB acquisition, accompanied by interruption of CRAB transmission can be achieved. Such an intervention, demanding increased manpower and resources, could not have been executed without hospital and ward management support.…”
Section: Discussionsupporting
confidence: 69%
“…Successful interventions in reducing CRAB have been published previously, [25][26][27] but their focus was mostly in ICUs. One study from Korea described a hospital-wide intervention focusing on hand hygiene campaign and cohorting patients with CRAB.…”
Section: Discussionmentioning
confidence: 99%
“…The use of standard plus contact precautions, associated to the cleaning of the environment, have been pointed out as multifaceted strategies to reduce the dissemination of resistant microorganisms in ICUs. To this end, the need to develop practices to encourage adhering to these practices in health institutions is reiterated (2,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found it crucial. 39 Australia's first National Antimicrobial Resistance policy for 2015~2019 mentions the demand for resources to sustain the implementation of AMS in all hospitals. 40 One study revealed that the incidence of MDRAB was addressed by controlling the inappropriate duration of antimicrobial treatments and the misuse of carbapenems.…”
Section: Discussionmentioning
confidence: 99%